2023
DOI: 10.55927/mudima.v3i2.2378
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Role of Product Quality and Brand Image on the Purchase Decision of Customers of Shoes Products in Jakarta

Abstract: The purpose of this study was to determine and analyze the effect of brand image on the decision to purchase Vans brand shoes. The second is to find out and analyze the influence of product quality on purchasing decisions for Vans brand shoes. The quantitative method is the preferred approach in this research. Researchers collected data through questionnaires. The population in this research are people who have bought Vans shoes in Jakarta. Determination of the sample used is a non-probability sampling techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Similarly, Mujanah and Satriatama (2022) found that brand image significantly affects purchasing decisions (Mujanah and Satriatama, 2022). Moreover, Tannady et al (2023) state that brand image and product quality significantly affect purchasing decisions (Tannady et al, 2023). Dona et al ( 2022) indicated that brand image significantly influences purchasing decisions.…”
Section: The Relationship Brand Image and Purchasing Decisionmentioning
confidence: 99%
“…Similarly, Mujanah and Satriatama (2022) found that brand image significantly affects purchasing decisions (Mujanah and Satriatama, 2022). Moreover, Tannady et al (2023) state that brand image and product quality significantly affect purchasing decisions (Tannady et al, 2023). Dona et al ( 2022) indicated that brand image significantly influences purchasing decisions.…”
Section: The Relationship Brand Image and Purchasing Decisionmentioning
confidence: 99%
“…Marketers will be able to improve these elements to increase their market share by using this study's analysis of the relationship between brand experience and customer happiness and brand loyalty. Tannady et al (2023) identified and assessed the influence of brand image on customers' decisions to purchase Vans footwear. The second is to determine and look at how product quality affects Vans brand shoe purchases.…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 99%
“…Hasil penelitian dari Chávez Zirena et al, (2020), Andiyani & Susandy, (2022), Carneiro et al, (2022), Mandiri et al, (2022), Özbölük & Akdoğan, (2022), Zirena-Bejarano et al, (2022), dan Hendy Tannady et al, (2023) menyatakan bahwa influencer secara positif dan signifikan mempengaruhi keputusan pembelian. Namun, pada hasil penelitian yang dilakukan oleh Wahyudi, (2022) menyatakan bahwa influencer tidak berpengaruh terhadap keputusan pembelian.…”
unclassified